Development of Solar Heater Boxes and Management of Callosobruchus Maculatus Fabricius (Coleoptera: Bruchidae) on Seed Adzuki Bean - Elbashier Elhada, Ragaa Mohammed (2011)
The selection and evaluation of solar heater boxes for trapping solar energy to disinfest legume grains was described. The effectiveness of five materials (cardboard, plywood, Perspex timber and metal) was investigated.Results showed that, cardboard and plywood were the best materials for seed treatment as they trap and retained more heat compared to Perspex and timber solar heater boxes. In addition, they are cheaper and easier to handle compared to metal. It was also concluded that, aluminum foils combined with black paint was the best lining than if aluminum foils or black paint used separately. The effect of seed depth on solar energy trapping inside cardboard and plywood solar heater boxes was also evaluated. Temperatures trapped in cardboard solar heater boxes with 7 kg of adzuki bean seeds were 53.3°C which was 13.9% higher than temperature trapped in plywood solar heater boxes. The effect of solar heat on development of C. maculatus was evaluated. A temperature of 66.4°C was achieved in solar heater boxes within 15 minutes which caused 100% mortality of adults and 4th larval instars. Egg hatchability decreased by 70% and 66.7% in plywood and cardboard respectively compared with untreated eggs. To verify the effect of solar temperatures, another experiment was done using the oven. Results showed that, times needed for 100% adult’s mortality were 10, 20, 50 and 70 minutes with temperatures of 70, 60, 50 and 40°C respectively. The effect of solar heat on seed quality of adzuki beans V. angularis was also determined. Results showed that, exposure to cardboard and plywood solar heater boxes did not show enormous effect on germination characters for adzuki bean seeds. In addition, experiment in oven was done for more verification. Exposure to temperatures of to 40, 50, 60, and 70°C did not affect germination of adzuki bean seeds. The effectiveness of cardboard solar heater boxes and a method using direct sun exposed seeds covered with plastic (open method) in trapping solar energy was evaluated. The influence of these methods on development of C. maculatus and seed quality of adzuki bean seeds was determined. Results showed that, cardboard solar heater boxes trapped temperature mean 11.6% higher than the temperature mean trapped in the open method. Both methods affect the development of C. maculatus. Percentage of adult mortality of 26.7% was caused by the open method compared to 46.7% adult mortality for cardboard solar heater boxes. Complete mortality occurred for eggs treated in cardboard solar heater boxes. Cardboard solar heater boxes could trap solar radiation and retained heat as much as possible compared to open method. Both methods have no adverse effect on seed quality of adzuki bean seeds.